Pendidikan Islam sebagai Ruang Publik: Studi tentang Partisipasi Siswa dalam Pengambilan Keputusan Sekolah di Madrasah Ainul Falah - Bukhari, Ach Baidlawi; Solichin, Mohammad Muchlis; Syarif, Zainuddin; Hasan, Nor; Hasan, Mohammad (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Islamic education serves not only as a means of transferring religious knowledge but also as a social space that shapes students’ character, values, and democratic awareness. This article aims to analyze how Islamic education can function as a public space that enables student participation in decision-making processes within the school environment. This study employs a qualitative approach using a case study method at Madrasah Ainul Falah. Data were collected through observation, interviews, and documentation involving teachers, students, and school administrators. The findings indicate that student participation in school decision-making can enhance democratic awareness, social responsibility, and leadership skills among students. Furthermore, the practice of deliberation implemented in student organization activities and madrasah discussion forums serves as a vehicle for democratic education that aligns with Islamic values. Thus, Islamic education holds great potential to become a public sphere that fosters a democratic culture rooted in Islamic values.